2011
DOI: 10.1095/biolreprod.110.085340
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Treatments with Fulvestrant and Anastrozole Differentially Affect Gene Expression in the Rat Efferent Ductules1

Abstract: Estrogen plays a key role in maintaining the morphology and function of the efferent ductules. We previously demonstrated that the antiestrogen fulvestrant markedly affected gene expression in the rat efferent ductules. The mechanism of fulvestrant action to modulate gene expression may involve not only the blockade of ESR1 and ESR2 estrogen receptors, but also the activation of ESR1 and ESR2 when the receptors are tethered to AP-1 or SP1 transcription factors, or the activation of the G protein-coupled estrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 94 publications
1
16
1
1
Order By: Relevance
“…However, this receptor was more widely expressed during regression, and it was detected in most connective cells and smooth muscle cells surrounding the efferent ductules of A. lituratus. These data are in agreement with other studies that revealed interstitial components of efferent ductules as a molecular target for estrogen modulation [15,52]. A greater number of positive connective and muscle cells was also found in the regressive rete testis [38] and epididymis (present result) of A. lituratus.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, this receptor was more widely expressed during regression, and it was detected in most connective cells and smooth muscle cells surrounding the efferent ductules of A. lituratus. These data are in agreement with other studies that revealed interstitial components of efferent ductules as a molecular target for estrogen modulation [15,52]. A greater number of positive connective and muscle cells was also found in the regressive rete testis [38] and epididymis (present result) of A. lituratus.…”
Section: Discussionsupporting
confidence: 94%
“…A constitutive expression of ERb in the efferent ductules of rats was previously described [36]. Unaltered ERb expression in other male genital organs submitted to different experimental designs has also been found [2,3,11,15,40,42,48]. During the annual reproductive cycle of hibernating bats, there is a drastic change in testosterone, but not dihydrotestosterone (DHT), and androstenedione levels [26].…”
Section: Regionmentioning
confidence: 92%
“…NPTX1 and GLP1R are involved in endocrine pathways that have been linked to CRC. NPTX1 is downregulated by pharmacological inhibition of estrogen signaling, indicating that NPTX1 is a downstream effector of estrogen (Gomes, et al 2011; Yasuhara, et al 2008). Estrogen has been suggested to protect against CRC development (Hogan, et al 2009; Lin, et al 2011), and epigenetic inactivation of estrogen receptor alpha (ESR1) has been widely observed in colonic mucosae of aged individuals as well as in CRCs (Issa et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…암컷호르몬으로 알려져 있는 에스트로겐은 암컷뿐만 아니 라 수컷 내에서도 분비된다는 사실은 이미 1930년대에 밝혀져 있었다 [24].에스트로겐이 수컷 생식계에서도 발달, 분화, 성장 에 관여하는 중요한 조절인자로 작용한다는 것이 이제 연구를 통해 널리 알려져 있으며 [4], 지금에 와서는 수컷 생식계에서 중요한 역할을 한다는 것이 많은 연구자들의 도움으로 밝혀져 있다 [5,12,16,23]. (Fig.…”
Section: 서 론unclassified